Effect of sensory-motor intervention associated with skin-to-skin contact on neuromotor and clinical outcomes of preterm newborns: A randomized controlled trial - Mariane de Oliveira Nunes Reco; Andressa Lagoa Nascimento França; Priscila Rímoli de Almeida; Daniele Soares-Marangoni (PLoS ONE, 2025)
Objective To examine the effects of a physical therapy sensory-motor intervention combined with kangaroo skin-to-skin contact in clinically stable preterm newborns. Design, setting, and participants This randomized controlled trial included two parallel and balanced groups. Thirty-four preterm newborns (≤34 weeks gestation and low birth weight) who were hospitalized in a neonatal intermediate care unit were randomly assigned to either the experimental (EG) or control (CG) group. Only newborns with a poor repertoire, as determined by the Prechtl General Movements Assessment (GMA), were included. Interventions The intervention consisted of 10 sessions of 15-minute sensory-motor physical therapy followed by 60 minutes of skin-to-skin contact (EG), or 60 minutes of skin-to-skin contact only (CG). Outcome measures The primary outcome was the quality of general movements (GMs), assessed by the GMA during the writhing movements (WM) and fidgety movements (FM) phases. Secondary outcomes included weight gain, posture and muscle tone, behavioral state, length of hospital stay, and establishment and maintenance of breastfeeding. Vital signs and signs of respiratory distress were also monitored. Results Newborns gained weight, showed no signs of respiratory distress, and maintained stable vital signs during the interventions. Both groups exhibited similar proportions of normal and abnormal GMs at both the WM and FM phases. However, the EG group showed improved scores for popliteal angle and leg recoil after the intervention compared to the control group. Conclusions The neonatal physical therapy intervention was a clinically safe technique for stable preterm newborns. This technique may be recommended to promote the development of physiological flexor tone in the lower limbs, but it does not appear to provide advantages in improving the quality of GMs compared to skin-to-skin contact. Due to the non-confirmatory findings, this study should be considered a pilot. Trial registration REBEC identifier RBR-4wx7wp. Trial registered in the Brazilian Clinical Trials Registry (ReBec). ReBec is a Primary Registry in the WHO Registry Network. Trial nº. RBR-5n82tv. URL: http://www.ensaiosclinicos.gov.br/rg/RBR-5n82tv/